Relatives Education And Coping Toolkit - REACT. Study protocol of a randomised controlled trial to assess the feasibility and effectiveness of a supported self management package for relatives of people with recent onset psychosis - Dunn Graham; Larkin Warren; Chapman Lesley; Pinfold Vanessa; Wainwright Laura; Glentworth David; Lobban Fiona; Postlethwaite Adam; Haddock Gillian (BMC Psychiatry, 2011)
Abstract Background Mental health problems commonly begin in adolescence when the majority of people are living with family. This can be a frightening time for relatives who often have little knowledge of what is happening or how to manage it. The UK National Health Service has a commitment to support relatives in order to reduce their distress, but research studies have shown that this can lead to a better outcome for service users as well. Unfortunately, many relatives do not get the kind of support they need. We aim to evaluate the feasibility, acceptability and effectiveness of providing and supporting a Relatives' Education and Coping Toolkit (REACT) for relatives of people with recent onset psychosis. Methods The study is a randomised control trial. Trial Registration for Current Controlled Trials ISRCTN69299093. Relatives of people receiving treatment from the Early Intervention Service for psychosis are randomly allocated to receive either Treatment As Usual (TAU) or TAU plus the REACT intervention. The main aims of the study are to: (i) determine the acceptability of a supported self-management intervention; (ii) determine preference for type of support; (iii) assess the feasibility of the design; (iv) identify the barriers and solutions to offering support for self-management approaches within the NHS; (v) estimate the likely effect size of the impact of the intervention on outcome for relatives; (vi) gain detailed feedback about the barriers and solutions to using a self-management approach; (vii) describe the way in which the intervention is used. Outcomes will be assessed from baseline and at 6 month follow-up. Discussion The intervention is compared to current treatment in a sample of participants highly representative of relatives in routine early intervention services across the UK. The intervention is protocolised, offered within routine practice by existing staff and extensive process data is being collected. Randomisation is independent; all assessments are made by blind raters. The limitations of the study are the lack of control over how the intervention is delivered, the short follow-up period, and the lack of assessment of service user outcomes. Despite these, the findings will inform future effectiveness trials and contribute to the growing evidence base for supported self-mangement interventions in mental health.